Coral garden conservation and restoration: how host taxon and ex-situ maintenance affect the microbiome of soft and hard corals - Rola, Marcellina; Coelho, Márcio A. G.; Pruckner, Christian; Quiroga-Pérez, Manuela; Stock, Willem; Baylina, Núria; Engelen, Aschwin H.; Wägele, Heike; Serrão, Ester A.; Frade, Pedro R. (Frontiers in Microbiology, 2025)
Temperate coral gardens are dense coral formations, which support rich marine species diversity, enabling benthic-pelagic coupling. Over the past decades, coral gardens have been increasingly threatened by bottom fishing, oil and gas exploitation, and climate change. Microbiome research bears great potential for assisted resilience in targeted conservation and restoration approaches. Yet, fundamental parameters of the coral garden microbiome remain poorly understood. Here, we provide a first broad record of bacterial communities associated with NE Atlantic coral garden corals and their community changes as response to human maintenance in conservation research. Octocorals (10 species), scleractinians (2 species) and one black coral species, were opportunistically collected from fisheries bycatch at 60–480 m depth around Cape St. Vincent (SW Portugal). Metabarcoding of the 16S-rRNA gene using third-generation sequencing revealed a high microbial host-specificity in the wild-collected coral species analyzed, and supported the importance of bacterial families Endozoicomonadaceae (mean relative abundance ± SE; 28.3 ± 10.5%), Spirochaetaceae (8.2 ± 5.8%) and Spongiibacteraceae (4.6 ± 1.8%). Endozoicomonadaceae were particularly dominant in the octocoral order Malacalcyonacea (67.7 ± 14.5%). The low microbial alpha diversity and limited interspecies differences among the Malacalcyonacea species suggest a conserved microbiome within this group, as compared to orders Scleralcyonacea, Antipatharia, and Scleractinia. Microbial responses to ex-situ maintenance of two branching octocoral species, Eunicella verrucosa and Paramuricea cf. grayi (Order Malacalcyonacea), were investigated (1) over 45 days under standardized aquaria conditions in the research station (Ramalhete Marine Station, CCMAR) and (2) over long-term captivity in two public aquaria, Oceanário de Lisboa and Zoomarine. Eunicella verrucosa displayed a stronger microbial community shift to short-term captivity (45 days), in contrast to greater microbiome stability in P. cf. grayi. However, long-term captivity in public aquaria led to microbiome shifts in both species. The strong host specificity of microbial diversity and its response to maintenance indicate that conservation and restoration of coral gardens require taxon-specific strategies.